Antimony sulfide as a light absorber in highly ordered, coaxial nanocylindrical arrays: preparation and integration into a photovoltaic device - Wu, Yanlin; Assaud, Loic; Kryschi, Carola; Capon, Boris; Detavernier, Christophe; Santinacci, Lionel; Bachmann, Julien (Journal of Materials Chemistry A, 2015)
We demonstrate the preparation of functional 'extremely thin absorber' solar cells consisting of massively parallel arrays of nanocylindrical, coaxial n-TiO2/i-Sb2S3/p-CuSCN junctions. Anodic alumina is used as an inert template that provides ordered pores of 80 nm diameter and 1-50 mu m length. Atomic layer deposition (ALD) then coats pores of up to 20 mm with thin layers of the electron conductor and the intrinsic light absorber. The crystallization of the initially amorphous Sb2S3 upon annealing is strongly promoted by an underlying crystalline TiO2 layer. After the remaining pore volume is filled with the hole conductor by solution evaporation, the resulting coaxial p-i-n junctions display stable diode and photodiode electrical characteristics. A recombination timescale of 40 ms is extracted from impedance spectroscopy in open circuit conditions, whereas transient absorption spectroscopy indicates that holes are extracted from Sb2S3 with a lifetime of 1 ns.